2011
DOI: 10.1097/acm.0b013e3182223b76
|View full text |Cite
|
Sign up to set email alerts
|

Job Characteristics and Job Satisfaction Among Physicians Involved With Research in the Veterans Health Administration

Abstract: Involvement with research was associated with more favorable job characteristics and job satisfaction perceptions among physicians in VA. Although there is a time and opportunity cost involved with research, medical centers that provide physicians with the opportunity to conduct research may have a more satisfied workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Similarly, participation in certain types of research (e.g., clinical trials) may involve more in-depth interactions with patients, which could lead to higher satisfaction with professional life. Previous research found that spending time in research contributes to higher job satisfaction among physicians [3, 18]. Research opportunities for neurology residents may stimulate research participation during subsequent careers and subsequently increase job satisfaction [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, participation in certain types of research (e.g., clinical trials) may involve more in-depth interactions with patients, which could lead to higher satisfaction with professional life. Previous research found that spending time in research contributes to higher job satisfaction among physicians [3, 18]. Research opportunities for neurology residents may stimulate research participation during subsequent careers and subsequently increase job satisfaction [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although recruiting medical students to pursue training in neurology provides one opportunity for increasing the supply of practicing neurologists [2], retaining those already in practice reduces the number exiting the field, thus supporting overall supply. Retaining neurologists depends, in part, on their professional life satisfaction; those satisfied with their career may opt to stay in practice while those dissatisfied may retire or reduce the number of clinic hours [35]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Task autonomy and performance feedback were found by Mohr and Burgess (2011) to influence job satisfaction. Hadi and Adil (2010) pointed out that skill variety, task significance, and task identity were related to job satisfaction.…”
Section: Job Characteristics and Job Satisfactionmentioning
confidence: 99%
“…Apart from improving job prospects and election to medical honor societies, doing clinical research enables the development of critical thinking skills that may prove lifesaving for your patients and provide a higher level of job satisfaction as a physician. 1 While the choice of clinical versus basic research is a personal one, clinical research has the added benefit of direct interaction with patients and arguably relates better with ongoing clinical training. The Accreditation Council for Graduate Medical Education (ACGME) expects trainees to participate in research and for residency programs to document such activity.…”
mentioning
confidence: 99%